SPBM MELALUI MODEL INKUIRI DALAM MATERI LINGKUNGAN SEHAT DAN TIDAK SEHAT UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS 3 SEMESTER 1 SDN KARANGSAMBIGALIH I - Sumiati Sumiati (Program Pascasarjana Universitas Islam Darul `Ulum Lamongan, 2022)
This study aims to answer whether the application of SPBM through inquiry models in healthy and unhealthy environmental materials can improve student learning outcomes in semester 1 of SDN Karangsambigalih II SDN Karangsambigalih II, Sugio District, Lamongan Regency, Academic Year 2016/2017